2014
DOI: 10.1007/s11661-014-2403-1
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Study of Binary and Ternary Nb3(X,Y) A15 Intermetallic Phases (X,Y = Al, Ge, Si, Sn)

Abstract: Elastic and thermodynamic properties of binary and ternary A15 phases containing Al, Ge, Si and Sn were studied using the first-principles pseudopotential plane-wave method based on density functional theory. The temperature dependence of the enthalpy of formation for the A15 intermetallics is reported using the quasiharmonic approximation. Elastic properties of the studied compounds were calculated at T = 0 K and were in agreement with the measured values reported in the literature. The elastic properties and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 58 publications
(58 reference statements)
1
7
0
Order By: Relevance
“…Such a result is in good compliance with the Cauchy pressure of Ti 3 Ir provided by Rajagopalan [34]. Similarly, other A15 cubic crystals (i.e., V 3 X (X = Si and Ge) [13], Nb 3 X (X = Al, Ge, Si and Sn) [10] and Nb 3 X (X = Al, Ga, In, Sn and Sb) [42]) have ductile characters owing to their positive Cauchy pressures.…”
Section: Elastic Constantssupporting
confidence: 73%
See 1 more Smart Citation
“…Such a result is in good compliance with the Cauchy pressure of Ti 3 Ir provided by Rajagopalan [34]. Similarly, other A15 cubic crystals (i.e., V 3 X (X = Si and Ge) [13], Nb 3 X (X = Al, Ge, Si and Sn) [10] and Nb 3 X (X = Al, Ga, In, Sn and Sb) [42]) have ductile characters owing to their positive Cauchy pressures.…”
Section: Elastic Constantssupporting
confidence: 73%
“…For example, Pan et al [9] reported the mechanical and electronic properties of Nb 3 Si using the first-principles method. By combining the first-principles method with quasi harmonic approximation, Papadimitriou et al [10][11][12] critically investigated the mechanical and thermodynamic properties of Nb 3 X (X = Al, Ge, Si and Sn). Chihi et al [13] theoretically evaluated the elastic and thermodynamic properties of V 3 X (X = Si, Ge and Sn) intermetallics utilizing the first-principles calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the modification in crystal structure can be determined using strain tensor ε ij. The generalized form of Hook's law, relating these two tensors, is given as σ ij = C ijkl ε kln , where the quantity C ijkl ε kl characterize the stiffness of material . The elastic constants are fundamentally important under different conditions because they provide worthy knowledge about mechanical steadiness and binding characteristics .…”
Section: Resultsmentioning
confidence: 99%
“…The generalized form of Hook's law, relating these two tensors, is given as σ ij = C ijkl ε kln , where the quantity C ijkl ε kl characterize the stiffness of material. 37 The elastic constants are fundamentally important under different conditions because they provide worthy knowledge about mechanical steadiness and binding characteristics. 38 The elastic constants are computed by energy-strain relation; this is done by applying strains in small amounts to the equilibrium structure and analyzing the change in the total energy.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…The properties of unalloyed A15–Nb 3 X (X = Al, Ge, Si, Sn) intermetallics that can form in Nb–silicide-based alloys were studied in [ 28 , 30 , 31 , 32 , 33 ]. The moduli of elasticity of A15 intermetallics are not unusually high.…”
Section: Introductionmentioning
confidence: 99%